Effect of tofacitinib exposure in utero and during breastfeeding on the immune status of exposed child - Mitrova, Katarina; Kostrejova, Marta; Zdychyncova, Kristyna; Lukas, Milan; Duricova, Dana (Journal of Crohn's and colitis, 2025)
BACKGROUND AND AIMS: Janus kinase (JAK) inhibitors, such as tofacitinib, are potent anti-inflammatory agents used in the treatment of ulcerative colitis (UC). Current guidelines recommend avoiding their use during pregnancy due to safety concerns, as well as during breastfeeding due to the potential excretion into breast milk. METHODS: This case report describes the impact of in utero exposure to tofacitinib during pregnancy and subsequent exposure via breastfeeding on the immune development of the exposed infant. RESULTS: A 37-year-old woman with UC, who was being treated with tofacitinib and vedolizumab, became pregnant and continued both medications, with the tofacitinib dosage reduced from 10 to 5 mg BID at gestational week 28. The infant was born healthy, with normal growth and development, and received all scheduled non-live vaccinations. At 15 months, immune parameters-including response to vaccination-were evaluated. The results showed normal immunoglobulin levels and an adequate serologic response to vaccination, with no signs of immune dysfunction. CONCLUSIONS: This case suggests that prolonged prenatal and postnatal exposure to tofacitinib may not adversely affect infant immune development. However, caution is advised due to the limited number of documented cases. Further research is needed to fully understand the long-term implications of JAK inhibitor exposure during pregnancy and breastfeeding.
Keywords: ulcerózní kolitida; Piperidines; Prenatal Exposure Delayed Effects; Pyrroles; komplikace těhotenství; zpožděný efekt prenatální expozice; Infant; Pregnancy; Breast Feeding; těhotenství; Adult; Pyrimidines; inhibitory Janus kinas; dospělí; Pregnancy Complications; Janus Kinase Inhibitors; inhibitory proteinkinas; piperidiny; pyrroly; kojení; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; novorozenec; lidé; ženské pohlaví; Humans; pyrimidiny; Infant, Newborn; kojenec; Protein Kinase Inhibitors; Colitis, Ulcerative; Female